Films and destinations—towards a film destination: A review. - Domínguez-Azcue, Janire; Almeida-García, Fernando; Pérez-Tapia, Gema; Cestino-González, Estefanía (MDPI, 2021)
The destination image is a complex construction in which the different sources of information consulted are decisive. Among these information sources, we can find films, which have a relevant function to create destination images. Films are one of the factors that most influences people in their motivation to travel to a destination. The academic literature on film tourism has grown considerably in recent years, but an updated revision is needed. Due to this fact, the main contribution of this paper is the proposal of an updated review of the academic literature focused on film tourism and destinations and their management implications. The general objective of this research is to analyse the existing literature, systematising the relationships that exist between films, film tourism, destination image, and tourist destination. To this end, a systematic review of the literature has been carried out, with two aims: on the one hand, a review of the existing literature from a descriptive perspective, showing the main publications, authors and topics, and on the other hand, a review from a thematic perspective. The results of the latter will be addressed in the discussion and conclusions. The results of the descriptive analysis highlight the significant growth in the literature analysed over the last 45 years, especially between 2005 and 2015. They also underline that the most studied topics are film destinations, marketing and destination image. The results of the thematic analysis highlight the importance of films and series as important information sources on the creation of destination images. The thematic analysis also provides information on the negative and positive aspects of film destination management.
Keywords: Turismo - Aspectos económicos; Cine; Marketing; Film tourism